2021
DOI: 10.1007/s40279-020-01418-1
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of Injury and Illness Among Trail Runners: A Systematic Review

Abstract: Author contributorship: Carel T. Viljoen -Conception and design of the study, literature search, review of literature for final inclusion of relevant studies, data extraction, level of evidence rating of included studies, quality assessment of included studies, data interpretation, manuscript write-up, manuscript editing Dina C. Janse van Rensburg -Conception and design of the study, review of literature for final inclusion of relevant studies, data extraction, manuscript editing Evert Verhagen -Conception and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 54 publications
2
26
0
3
Order By: Relevance
“…Most cases are related to common viral infections and allergic responses [9]. A recently published systematic review [6] showed that the most common trail running illnesses reported related to the gastrointestinal tract, followed by the metabolic and cardiovascular systems. These illnesses were only analyzed during competition but not during the training period leading up to the competition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most cases are related to common viral infections and allergic responses [9]. A recently published systematic review [6] showed that the most common trail running illnesses reported related to the gastrointestinal tract, followed by the metabolic and cardiovascular systems. These illnesses were only analyzed during competition but not during the training period leading up to the competition.…”
Section: Discussionmentioning
confidence: 99%
“…Kluitenberg et al [5] described the prevalence of injuries in different populations of runners depending on their experience and type of competition, reporting a prevalence of 16.7 to 84.9% in novices, 21.6 to 55.0% in recreational runners, 1.4 to 94.4% in cross country runners and 21.0 to 90.6% in ultra-distance runners [5]. A recently published systematic review [6] showed an overall incidence range between 1.6-4285.0 injuries per 1000 h of running. Additionally, the prevalence of injuries in trail runners has been reported between 22.2% [7] during competition and 28.2% [8] over one year with the lower limbs the most susceptible to sustain injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the positive health benefits of running and outdoor activities, trail running presents a high risk of injury during race [ 2 , 3 ] and training participation [ 4 ]. The majority of trail running literature investigating injury is focused on outcomes related to race participation, with limited studies reporting on training-related injuries [ 5 ]. A prospective cohort study among Dutch trail runners reported an overall incidence of 10.7 running-related injuries (RRIs) per 1000 h, showing a higher incidence of overuse (8.1 per 1000 h) vs. acute (2.7 per 1000 h) RRIs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…
On 17 March 2021, an erratum was published online [1] in the International Journal of Sports Medicine that showed corrected values for the incidences of injury and illness presented in the Vernillo et al study [1]. The Vernillo et al study was included in our systematic review [2] and therefore the following updates should be applied:
…”
mentioning
confidence: 99%